2011
DOI: 10.1051/0004-6361/201016361
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of M 2–9 from 2000 to 2010

Abstract: Context. Understanding the formation of collimated outflows is one of the most debated and controversial topics in the study of the late stages of stellar evolution. Aims. M 2-9 is an outstanding representative of extreme aspherical flows. It presents unique features such as a pair of high-velocity dusty polar blobs and a mirror-symmetric rotating pattern in the inner lobes. Their study provides important information on the nature of the poorly understood central source of M 2-9 and its nebula. Methods. Imagin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 22 publications
(55 reference statements)
3
47
1
Order By: Relevance
“…Its bipolar structure contains two separate shells, an inner bulb and an outer neutral shell (Corradi et al 2011), which are thought to be formed from two equatorial rings/tori (Castro-Carrizo et al 2012) found at the nebula's centre. The nebula also has a feathered component which extends all the way out to a pair of dusty blobs.…”
Section: Morpho-kinematic Modelling Of M 2−9mentioning
confidence: 99%
See 2 more Smart Citations
“…Its bipolar structure contains two separate shells, an inner bulb and an outer neutral shell (Corradi et al 2011), which are thought to be formed from two equatorial rings/tori (Castro-Carrizo et al 2012) found at the nebula's centre. The nebula also has a feathered component which extends all the way out to a pair of dusty blobs.…”
Section: Morpho-kinematic Modelling Of M 2−9mentioning
confidence: 99%
“…Here, two well known extreme bPNe (M 2−9 and Mz 3) and one confirmed symbiotic nebula (Hen 2−104) are investigated. It has been proposed that a SySt mechanism has led to the formation of M 2−9 (Doyle et al 2000;Livio & Soker 2001;Schmeja & Kimeswenger 2001;Smith & Gehrz 2005;Corradi et al 2011), Mz 3 (Schmeja & Kimeswenger 2001;Guerrero et al 2004;Smith & Gehrz 2005), and Hen 2−104 (Whitelock 1987;Lutz et al 1989;Schwarz et al 1989;Corradi et al 2001;Santander-García et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique property of this object is its 90-yr rotating pattern in the inner lobes. Given its corkscrew geometry and associated travelling times, excitation structure, we conclude that the phenomenon is caused by a particle jet from the central source hitting and exciting the walls of the inner lobes of M2-9 (Corradi et al 2011). The speed of the jet -between 11000 and 16000 km s −1 -would be unusually high among PNe and symbiotic stars.…”
mentioning
confidence: 99%
“…Nebulae have also been discovered around symbiotic stars that harbor non-Mira cool giants: AS 201 (Schwarz 1991) and CH Cyg (Corradi et al 2001b). Bipolar planetary nebulae like M 2-9 (Corradi et al 2011) and Mz 3 (Guerrero et al 2004;Santander-García et al 2004) that may possibly host a symbiotic nucleus (Schmeja & Kimeswenger 2001) are relevant bridges between symbiotic binaries and aspherical planetary nebulae.…”
Section: Introductionmentioning
confidence: 99%